Charged particle multiplicity in three-jet events and two-gluon systems - Abdallah, J; Abreu, P; Adam, W; Adzic, P; Albrecht, T; Alderweireld, T; Alemany-Fernandez, R; Allmendinger, T; Allport, P; Amaldi, U; Amapane, N; Amato, S; et al. (2005)
The charged particle multiplicity in hadronic three-jet events from Z decays is investigated. The topology dependence of the event multiplicity is found to be well described by a modified leading logarithmic prediction. A parameter fit of the prediction to the data yields a measurement of the colour factor ratio CA/CF with the result CA/CF = 2.261 ± 0.014stat. ± 0.036exp. ± 0.066theo. in agreement with the SU(3) expectation of QCD. The quark-related contribution to the event multiplicity is subtracted from the three-jet event multiplicity resulting in a measurement of the multiplicity of twogluon colour-singlet states over a wide energy range. The ratios r = Ngg(s)/Nqq̄(s) of the gluon and quark multiplicities and r(1) = N′gg(s)/N′qq̄(s) of their derivatives are compared with perturbative calculations. While a good agreement between calculations and data is observed for r(1), larger deviations are found for r indicating that non-perturbative effects are more important for r than for r(1). © Springer-Verlag / Società Italiana di Fisica 2005.